Ta có \(-x+\sqrt{x}+2=-\left(\left(\sqrt{x}\right)^2-2.\sqrt{x}.\frac{1}{2}+\left(\frac{1}{2}\right)^2\right)-\frac{7}{4}\)=\(-\left(\sqrt{x}-\frac{1}{2}\right)^2-\frac{7}{4}\) cái dấu ll là dấu tùm bậy đừng có để í Ta có \(-\left(\sqrt{x}-\frac{1}{2}\right)^2=<0vớimoix=>-\left(\sqrt{x}-\frac{1}{2}\right)^2-\frac{7}{4}=<\frac{7}{4}\)với mọi x
dấu ''='' xảy ra <=> \(\sqrt{x}-\frac{1}{2}=0\)<=> x= 1/4 Vậy với x =1/4 thì gtln của biểu thức là -7/4
gtln của \(-x+\sqrt{x}-2\) là \(\infty\)
\(A=-\frac{3}{4}-\left(x-\sqrt{x}+\frac{1}{4}\right)=-\frac{3}{4}-\left(\sqrt{x}-\frac{1}{2}\right)^2\) Max\(A=-\frac{3}{4}\) khi \(\sqrt{x}=\frac{1}{2}\) hay \(x=\frac{1}{4}\)